2018
DOI: 10.6001/energetika.v64i3.3805
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of systematic errors of a non-invasive intracranial pressure measurement

Abstract: Intracranial pressure (ICP) monitoring procedure can be applied to aid in secondary brain damage prevention. A high invasiveness of commonly used ICP measuring methods poses a risk of complications, and therefore new non-invasive methods are currently being developed. A promising non-invasive ICP measurement method is based on the existence of pressure balance state, which is driven by the unique morphological property of ophthalmic artery (OA). The value of ICP can be obtained by evaluating blood flow or arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Previous studies showed that the systematic error of the modeled ICP non-inv monitoring based on the blood velocity was within the limits of [1.6, 1.8] mmHg for the idealized straight OA and [0.04, 4.6] mmHg for the subject-specific curved OA 29 , 30 , which are similar to the value of ± 1.0 mmHg obtained in this study. The current state of the neuroimaging techniques allows for the implementation of subject-specific models considering the OA branching from the internal carotid artery.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that the systematic error of the modeled ICP non-inv monitoring based on the blood velocity was within the limits of [1.6, 1.8] mmHg for the idealized straight OA and [0.04, 4.6] mmHg for the subject-specific curved OA 29 , 30 , which are similar to the value of ± 1.0 mmHg obtained in this study. The current state of the neuroimaging techniques allows for the implementation of subject-specific models considering the OA branching from the internal carotid artery.…”
Section: Discussionsupporting
confidence: 89%